PEMANFAATAN MEDIA DIGITAL PADA GURU SD DI KOTA BLITAR - Lilik Handayani; Henry Praherdhiono; Candra Utama (LPPM Institut Pendidikan Nusantara Global, 2022)
In the era of digitalization of the 21st century, the ability of teachers to master digital-based learning is a must in efforts to improve the competence of teachers and students. The purpose of this study is to analyze various digital media that teachers use during online learning and after. This research was conducted by survey method. The subject of this study involved a sample of 6th grade teachers in Blitar City, totaling 55 teachers consisting of 14 male teachers and 41 female teachers with an age range of 26 - 59 years. All of the teachers involved in this study teach in both public and private schools in Blitar City. There are 4 teachers with less than five years of teaching experience, 18 teachers with five to ten years of teaching experience, 10 teachers of eleven to fifteen years of teaching experience and 23 teachers who teach more than fifteen years. Data collection is done by filling out the Google form. Data analysis was carried out simultaneously and integrated descriptively. Based on the findings above, it can be concluded that all teachers in Blitar City or 55 people use WA as a learning application. WA is also the most frequently used application with usage reaching 94.5% or 52 out of 55 survey fillers. Meanwhile, the application with the least number of users was Classpoint, which was chosen by 2 out of 55 people or around 3.6%. Classpoint and Edpuzzle are also applications that are rarely used. Ease of use is the most common reason for grade 6 teachers in Blitar City to choose learning applications, this can be seen from the data of around 37 out of 55 teachers or around 84.1%.